High Complaints of Lower Back Pain Related to Length of Service Among Workers at the Ud. Berkah Gemilang Magetan Bread Factory - Pipid Ari Wibowo; Widiarini, Retno; Fitriani, Sonia (Jurnal Kesmas Prima Indonesia, 2025)
Low back pain (LBP) is a musculoskeletal disorder frequently experienced by workers, primarily due to ergonomic factors and work duration. This study aims to analyze the relationship between work duration and low back pain complaints among workers at the UD. Berkah Gemilang Magetan bakery. The study design used a quantitative approach with a cross-sectional design. The study sample consisted of 35 workers, selected using a simple random sampling technique. Data were collected through the Nordic Body Map (NBM) questionnaire and analyzed using the Kendall Tau-b correlation test. The results showed that the majority of workers had a work period of ≥ 3 years (54.3%) and experienced low back pain complaints in the moderate risk category. Statistical analysis showed a significant relationship between work duration and low back pain complaints (ρ = 0.003; CC = 0.491). The longer the work period, the higher the risk of workers experiencing low back pain complaints, especially in the thighs, knees, and feet. The conclusion is that a longer work period increases the risk of low back pain in workers. Suggestions include the application of ergonomic principles, training in correct work postures, and regular health checks to prevent and reduce these risks.   Kata kunci: Nyeri punggung bawah, masa kerja, ergonomi, pekerja pabrik